Analysis of Low Interest in Reading in Grade IV Elementary School Students - Kamasiah Kamasiah (Jurnal Wawasan Sarjana, 2023)
The purpose of this study was to find the factors causing the low interest in reading at Public Elementary School 2 Lamangga in grade IV. This research is a qualitative and descriptive research. The subjects of this study amounted to four people. Data collection techniques as follows: 1) Observation, 2) Interview, 3) Documentation. Data analysis begins with data collection and then analyzed to determine the results. Upon further consideration, the statements made in this essay become clearer. Data analysis in the Miles and Huberman model qualitative research was carried out at the time the data collection took place, and after completing the data collection within a certain period. The results of this study revealed the factors causing the low reading interest of fourth grade students at Public Elementary School 2 Lamangga. Factors that reduce students' interest in reading are internal factors and external factors. Internal factors that cause students' low interest in reading are the nature and habits of these students. External factors that reduce students' interest in reading are books or reading materials, the school environment, and the family environment.